Terbinafine in the treatment of dermatophyte toenail onychomycosis: a meta‐analysis of efficacy for continuous and intermittent regimens. (28th May 2012) - Gupta, A.K.; Paquet, M.; Simpson, F.; Tavakkol, A.
Abstract Objective To compare mycological and complete cures of terbinafine continuous and intermittent regimens in the treatment of toenail onychomycosis. Methods The PubMed database was searched using the terms "terbinafine", "onychomycosis", "continuous" and "pulse(d)" or "intermittent". The inclusion criteria were head‐to‐head comparison of terbinafine pulse and continuous regimens for dermatophyte toenail infections. Risk ratios were calculated for intention‐to‐treat and evaluable patient analyses, when possible. Pooled estimates for total and subgroup analyses were calculated using a random effect model, Mantel‐Haenszel method and their probabilities were calculated with z‐statistics. Results Nine studies from eight publications were included. Two continuous regimens and four intermittent regimens were investigated. A pooled risk ratio of 0.87 was obtained for intention‐to‐treat (95% CI: 0.79–0.96, P = 0.004, n = 6) and evaluable patient (95% CI: 0.80–0.96, P = 0.003, n = 8) analyses of mycological cure, favouring continuous terbinafine. For complete cure, pooled risk ratios of 0.97 (95% CI: 0.77–1.23, P = 0.82, n = 7) for intention‐to‐treat and 0.93 (95% CI: 0.76–1.13, P = 0.44, n = 9) for evaluable patient analyses showed equality of the two regimens. The pulse regimen that demonstrated consistently comparable results to the continuous terbinafine regimen was two pulses of terbinafine 250 mg/day for 4 weeks on/4 weeks off. Conclusions Meta‐analysis of published studies of toenail onychomycosis showed that a continuous terbinafine regimen is generally significantly superior to a pulsed terbinafine regimen for mycological cure. In contrast, some pulse terbinafine regimens were as effective as continuous terbinafine regimens for complete cure.